(untitled) (Orfeu, 2020)
From the initial conception to the musical writing, there are many possible paths, some combine original techniques together with those from renowned composers. This article shows how a musical composition has been established deriving out the raw material obtained by the analysis of birdsong, its elaboration and the implications in time issue. In order to understand how it works an analysis of the piece Os pássaros no Delta do Jacuí (The birds in Jacuí’s delta) will be performed looking for the aspects related to poetics likewise compositional techniques all together with the help of theoretical references.